Análise da política de inclusão escolar na perspectiva das famílias de estudantes público-alvo da educação especial - Branco, Ana Paula Silva Cantarelli (2020)
The National Education Plan establishes that it is necessary to carry out studies to track the goals of educational policies. In this sense, the present study is part of a matrix project that aimed to undertake a multidimensional assessment, involving different actors of the educational policy of school inclusion in a municipal context. Based on the Policy Cycle Approach, and the state of the art of studies with families and the school inclusion policy, the objective of this study was to analyze the school inclusion policy in the context of a municipality from the perspective of the families of students with special educational needs (SEN). It was adopted a multimethod design with a view to triangulate data from interviews with families, analyze the context of text production (national and local policy), and the context of influence of the municipality. The analysis of the documents indicated a national policy based on the weakening of the role of the State in which the rights of minorities are silenced with an emphasis on outsourcing services to support the schooling of SEN students. In the municipality, there was a strong influence of the partnership between public authorities and a specialized philanthropic institution. To complete the policy analysis, 67 family members of students with SEN, who attended to seven different municipal schools were interviewed, using a questionnaire within a survey platform applied trough a tablet. The family members' responses to 55 items, grouped into 19 indicators and four major axes marked the analysis of the quality of the school inclusion policy by the family members. The general index for the evaluation of the school inclusion policy by family members was 6.2 (good). School indexes ranged from 5.1 (regular) to 7.8 (good), showing a discrepancy in the evaluation between schools by family members and inequality in the effects of the policy of the same municipality. The comparative analysis between axes showed a good evaluation of the specialized support service for students with SEN (7.6-good), the pedagogical and social relations of students with SEN and their families with schools (7.1-good), but less positive evaluations were found in the facilities infrastructure (6.0-regular), and in the culture and organization (4.1-regular) of these schools. We conclude that although the rates of support services offered and the pedagogical and social relations were good, the culture of participation and organization of schools need to improve. If family members' knowledge of politics expanded, this could provide them with qualified knowledge to influence more in the field of pedagogical recontextualization and, thus, produce alternative narratives that would contribute to advancing the effects of educational policies in reducing historical inequalities and promoting social justice. We hope that the present study will enable the monitoring of educational policies that will give voice to the families of SEN students